K-3[Fe3.26v0.74(Oh)O(Po4)(4)(H2o)(2)]Center Dot 2h(2)O: A Synthetic Leucophosphite - Venegas-Yazigi, D; Venegas-Yazigi, D (TAYLOR & FRANCIS LTD, 2013)
A new iron(III)/vanadium(III) phosphate, K-3[Fe3.26V0.74(OH)O(PO4)(4)(H2O)(2)]center dot 2H(2)O (1), has been obtained by hydrothermal synthesis and characterized by single crystal X-ray diffraction, Scanning electron microscopyenergy dispersive X-ray spectroscopy, Inductively coupled plasma atomic emission spectroscopy (ICP), thermogravimetric analysis, and FTIR spectroscopy. Single crystal X-ray diffraction reveals a 3D open framework (monoclinic, space group P2(1)/n, a=9.6391(7)angstrom, b=9.8063(7)angstrom, c=9.7268(7)angstrom, =100.71(1)degrees, and V=903.38(11)angstrom(3)). This structure presents Fe-III and V-III in a 4.4:1M ratio with the metal ions in two different crystallographic sites. Both metallic centers have distorted octahedral environments, linked by PO4 tetrahedra, forming channels along the a-axis. The asymmetric unit of K-3[Fe3.26V0.74(OH)O(PO4)(4)(H2O)(2)]center dot 2H(2)O presents a {M-4(OH)O(PO4)(4)(H2O)(2)}(3) anionic entity, charge balanced by three K+, which are located within the channels. It is also possible to distinguish M4O2 units whose M-III polyhedra are linked by vertex and edges.